Developing the TIC Grade: A Youth Self-Report Measure of Perceptions of Trauma-Informed Care. (November 2022) - Sinko, Laura; Beck, Dana; Seng, Julia
BACKGROUND: Service delivery organizations are advancing the provision of trauma-informed care (TIC) for youth to improve outcomes. However, currently there are no validated, reliable evaluation measures to capture the voices of adolescent clients and how well they perceive TIC implementation. AIMS: The purpose of this project was to create an evaluation measure with strong content validity for adolescent health and service users to give feedback to organizations about their implementation of TIC. This article outlines Step 1 of our instrument development, by discussing our process creating the measure and affirming content validity. Psychometric testing of this measure (Step 2) is described in a companion paper. METHODS: We combined deductive theory substruction with an inductive participatory process to create, revise, and finalize the measure. The National Center for Trauma-Informed Care's framework of four practices and six principles was substructed into an 18-item draft measure. A four-member community youth advisory board (CYAB) then worked to inductively modify our draft to provide age-appropriate clarity and ensure a nontriggering respondent experience. Finally, the CYAB members conducted cognitive interviews with 10 other adolescents in local evening data collection events, refining the measure for future psychometric testing. RESULTS: The process resulted in a 20-item form based on CYAB feedback. Refinements included providing an accessible definition of trauma, asking questions about trauma history, and asking whether trauma affected the client's visit on the day of service use. CONCLUSIONS: The CYAB involvement enhanced content validity and ensured a trauma-informed instrument development approach.